2008
DOI: 10.1007/978-1-60327-047-2_4
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach Using MALDI-TOF/TOF Mass Spectrometry and Prestructured Sample Supports (AnchorChip Technology) for Proteomic Profiling and Protein Identification

Abstract: Mass spectrometry (MS)-based proteomic profiling and protein identification has become a powerful tool for the discovery of new disease biomarkers. Among the MS platforms, matrix-assisted laser desorption/ionization time-of-flight/time-of-flight (MALDI-TOF/TOF) MS offers high sample throughput and the flexibility to couple with different off-line sample fractionation techniques. Here, we present a strategy using MALDI-TOF/TOF MS to analyze fractionated human serum samples for proteomic profiling and then ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…The use of ion exchangers such as DEAE followed by C18 produced further identifications of endogenous peptide ladders from more parent proteins compared to C18 alone (Marshall et al, 2003. The use of magnetic beads to capture blood peptides has been examined (de Noo et al, 2005(de Noo et al, , 2006aGatlin-Bunai et al, 2007;Tiss et al, 2007;Leung & Pitts, 2008;Yao et al, 2008;Callesen et al, 2008a;Qiu et al, 2009;Huang et al, 2009c). Packed chromatography resins were observed to outperform the use of loose media collected in the batch mode (Tiss et al, 2007).…”
Section: Preparative Chromatographymentioning
confidence: 95%
See 1 more Smart Citation
“…The use of ion exchangers such as DEAE followed by C18 produced further identifications of endogenous peptide ladders from more parent proteins compared to C18 alone (Marshall et al, 2003. The use of magnetic beads to capture blood peptides has been examined (de Noo et al, 2005(de Noo et al, , 2006aGatlin-Bunai et al, 2007;Tiss et al, 2007;Leung & Pitts, 2008;Yao et al, 2008;Callesen et al, 2008a;Qiu et al, 2009;Huang et al, 2009c). Packed chromatography resins were observed to outperform the use of loose media collected in the batch mode (Tiss et al, 2007).…”
Section: Preparative Chromatographymentioning
confidence: 95%
“…Recently, the use of parent ion separations in the gas phase was shown to increase both the sensitivity and the specificity of LC-MS/MS of blood (Liu et al, 2007c). Modified surfaces for MALDI plates might provide some advantages for the use of affinity reagents (Weinberger, Morris, & Pawlak, 2000;Weinberger et al, 2002;Leung & Pitts, 2008) and provide for rapid analysis (Corr et al, 2006). The robustness and sensitivity of mass spectrometry of blood is only likely to increase in the future, in part due to enhancements in the evolution, separation and capture of the products of ionization (Guzzetta, Thakur, & Mylchreest, 2002;Corr et al, 2006;Liu et al, 2007c;Kelly et al, 2008).…”
Section: Discovery By Lc-esi-ms/msmentioning
confidence: 99%
“…Prior studies of honeybee venom employing both "bottom-up" and "topdown" strategies led to identification of only six known venom proteins and three unknown protein components, not identified earlier (Matysiak et al, 2011b;Peiren et al, 2005). Although, PAC targets are dedicated for the rapid screening analysis, many reports have shown that application of the classical AnchorChip MALDI plate facilitates better results (Du et al, 2010;Leung and Pitts, 2008;Zhang et al, 2008Zhang et al, , 2007. This plate, according to the manufacturer is preferred for high-throughput MALDI measurements that are performed in unattended, fully automatic mode.…”
Section: Honeybee Venom Analysis Applying Shotgun Proteomic Approachmentioning
confidence: 98%
“…Since biomolecular profiling will reflect changes in developmental, physiological, and pathological processes [178][179][180][181][182][183][184][185], several approaches have used bimolecular profiling for valid clinical diagnoses. Multivariate analysis such as principal component analysis (PCA) is often involved in these approaches to efficiently identify differences in biomolecular patterns between samples [186,187].…”
Section: Detecting Disease Biomarkers In Biological Fluidsmentioning
confidence: 99%